International Society and Its Islamic Malcontents - Hashmi, Sohail H. (Tufts Archival Research Center, 2005)
Volume 20, Issue 1. Winter/Spring Contrary to the Western perception, the recent "Islamic revival" is defensive rather than offensive in nature. Rather than a challenge to the international community, it is an attempt by Muslim intellectuals and political activists to reclaim an Islamic civilization that they believe has gone astray.